2013
DOI: 10.1371/journal.pone.0070723
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function in Mlo Orthologs Reduces Susceptibility of Pepper and Tomato to Powdery Mildew Disease Caused by Leveillula taurica

Abstract: Powdery mildew disease caused by Leveillula taurica is a serious fungal threat to greenhouse tomato and pepper production. In contrast to most powdery mildew species which are epiphytic, L. taurica is an endophytic fungus colonizing the mesophyll tissues of the leaf. In barley, Arabidopsis, tomato and pea, the correct functioning of specific homologues of the plant Mlo gene family has been found to be required for pathogenesis of epiphytic powdery mildew fungi. The aim of this study was to investigate the invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 49 publications
5
115
0
Order By: Relevance
“…Therefore, CisMLOs may play roles as an important cross-talk node in both stress and hormone signaling processes. The MLO genes are reported to take part in programmed cell death, and in the PM pathogen responses [ 12,24 ], the biotrophic oomycete pathogen Hyaloperonospora arabidopsidis, as well as the hemibiotrophic bacterial pathogens, for example, Pseudomonas syringae pv. tomato and Xanthomonas campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CisMLOs may play roles as an important cross-talk node in both stress and hormone signaling processes. The MLO genes are reported to take part in programmed cell death, and in the PM pathogen responses [ 12,24 ], the biotrophic oomycete pathogen Hyaloperonospora arabidopsidis, as well as the hemibiotrophic bacterial pathogens, for example, Pseudomonas syringae pv. tomato and Xanthomonas campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…The recessive ol-2 gene (Ciccarese et al 1998;Bai et al 2008) identified in S. lycopersicum var. cerasiforme confers incomplete resistance to L. taurica (Zheng et al 2013b). …”
Section: Resistance To L Tauricamentioning
confidence: 99%
“…Inactivation of S-genes through gene-knockout, geneknockdown or virus induced gene-silencing has been proven a viable option for generating resistance genotypes against important diseases such as rice blast in rice (Oryza sativa) [7], citrus canker in citrus (Citrus paradisi) [8] and powdery mildew in grapevine (Vitis vinifera) [9], tomato and pepper [10]. Currently, two classes of PM S-genes are known, Mildew-Locus-O (MLO) genes and Powdery Mildew Resistance (PMR), both of which are loss-of-function genes [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Functional clade V MLO proteins negatively regulate defense pathways at the site of PM inoculation, thus allowing the pathogen to induce pathogenesis [11]. Therefore, a loss of function in MLO genes consequently induce resistance to PM [10,15]. PMR genes on the other hand are far less studied and most are putative, but some have been shown to play a role in PM susceptibility in Arabidopsis (AtPMR4, AtPMR5, and AtPMR6) and tomato (SlPMR4) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%